The effect of marine n-3 polyunsaturated fatty acids on cardiac autonomic and hemodynamic function in patients with psoriatic arthritis: a randomised, double-blind, placebo-controlled trial. Issue 1 (December 2016) - Kristensen, Salome; Schmidt, Erik; Schlemmer, Annette; Rasmussen, Claus; Lindgreen, Esther; Johansen, Martin; Christensen, Jeppe
Abstract Background The aim of this study was to investigate the effect of marine n-3 polyunsaturated fatty acids (PUFA) on cardiac autonomic function and vascular function in patients with psoriatic arthritis. Methods The study was conducted as a randomized, double-blind, placebo-controlled trial, where 145 patients with psoriatic arthritis were supplemented with 3 g of n-3 PUFA or olive oil (control) daily for 24 weeks. Blood pressure, heart rate, heart rate variability (HRV), central blood pressure, pulse wave velocity (PWV) and fatty acid composition of granulocytes, were determined at baseline and after supplementation. Results At baseline we found a significant difference in the mean of all normal RR intervals (inverse of heart rate, vary from beat to beat) when comparing subjects with the highest vs the lowest fish intake (p = 0.03). After supplementation for 24 weeks there was a trend towards an increase in RR (p = 0.13) and decrease in heart rate (p = 0.12) comparing the n-3 PUFA group with the control group. However, per-protocol analysis showed significantly increased RR (p = 0.01) and lowered heart rate (p = 0.01) in the n-3 PUFA supplemented patients compared with controls. Blood pressure, PWV and Central blood pressure did not change after supplementation with n-3 PUFA. Adjustment for disease activity and conventional cardiovascular risk factors did not change the results. Conclusions Marine n-3 PUFA increased RR intervals in patients with psoriatic arthritis which may suggest a protective effect of n-3 PUFA against cardiovascular disease in this population. Trial registration Clinicaltrials.gov Identifier:NCT01818804